Assessing Pedagogical Competence of Arabic Teachers: A Case Study of SDIT Permata Mulia Mojokerto - Saputra, Prayoga Ade; Ammar, Farikh Marzuki (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative-qualitative research study aimed to assess the pedagogical competence of Arabic teachers at SDIT Permata Mulia Mojokerto based on the standards outlined in the Regulation of the Minister of National Education Number 16 of 2007. The research employed a descriptive quantitative analysis to interpret the data obtained through questionnaires and observations. The results revealed that the pedagogical competence of Arabic teachers at SDIT Permata Mulia Mojokerto was categorized as